INTEGRASI SAINS DAN AGAMA DALAM PENDIDIKAN DITINJAU DARI PRESPEKTIF ISLAM - Nurasmah , Nurasmah; Kambali, Kambali (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The increasing role of science and religion in human life challenges the idea of secularization theory which predicts a decline in the influence of religion in modern society. This interaction has given rise to ongoing debate regarding the relationship between science and religion. This article aims to explore the integration of science and religion in education from an Islamic perspective. His research concerns center on understanding the current relationship between Islam and science, as well as attempting to bridge the gap between the two fields. This research uses a qualitative descriptive research design, focusing on library research and academic articles obtained from Google Scholar as primary data sources. These findings highlight the integral role of science and religion in human life, and emphasize the need for balance and harmony between the two. The conclusion emphasizes the important role of integrating Islamic education and knowledge into the world, with the 2013 curriculum emphasizing the impact, psychomotor and cognitive aspects of education. Islamic epistemology underscores the importance of knowledge and education in the Qur'an, positioning education as a fundamental aspect of human life.